Molecular Investigations of PenA-mediated β-lactam Resistance in Burkholderia pseudomallei - Rholl, Drew A.; Papp-Wallace, Krisztina M.; Tomaras, Andrew P.; Vasil, Michael L.; Bonomo, Robert A.; Schweizer, Herbert P. (Frontiers in Microbiology, 2011)
Burkholderia pseudomallei is the etiological agent of melioidosis. Because of the bacterium’s intrinsic resistance and propensity to establish latent infections, melioidosis therapy is complicated and prolonged. Newer generation β-lactams, specifically ceftazidime, are used for acute phase therapy, but resistance to this cephalosporin has been observed. The chromosomally encoded penA gene encodes a putative twin arginine translocase (TAT)-secreted β-lactamase, and penA mutations have been implicated in ceftazidime resistance in clinical isolates. However, the role of PenA in resistance has not yet been systematically studied in isogenetic B. pseudomallei mutant backgrounds. We investigated the effects of penA deletion, point mutations, and up-regulation, as well as tat operon deletion and PenA TAT-signal sequence mutations. These experiments were made possible by employing a B. pseudomallei strain that is excluded from Select Agent regulations. Deletion of penA significantly (>4-fold) reduced the susceptibility to six of the nine β-lactams tested and ≥16-fold for ampicillin, amoxicillin, and carbenicillin. Overexpression of penA by single-copy, chromosomal expression of the gene under control of the inducible Ptac promoter, increased resistance levels for all β-lactams tested 2- to 10-fold. Recreation of the C69Y and P167S PenA amino acid substitutions previously observed in resistant clinical isolates increased resistance to ceftazidime by ≥85- and 5- to 8-fold, respectively. Similarly, a S72F substitution resulted in a 4-fold increase in resistance to amoxicillin and clavulanic acid. Susceptibility assays with PenA TAT-signal sequence and ΔtatABC mutants, as well as Western blot analysis, confirmed that PenA is a TAT secreted enzyme and not periplasmic but associated with the spheroplastic cell fraction. Lastly, we determined that two LysR-family regulators encoded by genes adjacent to penA do not play a role in transcriptional regulation of penA expression.